2017
DOI: 10.1002/lary.26443
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant radiotherapy is not supported in patients with verrucous carcinoma of the oral cavity

Abstract: 2C. Laryngoscope, 127:1334-1338, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…VC is a well-differentiated, indolent tumor, and unlike oral cavity SCC, is rarely associated with regional or distant metastases. [4][5][6][7][8] Surgical resection remains the primary treatment modality for oral cavity VC, and rates of PORT range from 10% to 18%. 9,10 However, the benefit of PORT is unclear, and may actually reduce survival.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…VC is a well-differentiated, indolent tumor, and unlike oral cavity SCC, is rarely associated with regional or distant metastases. [4][5][6][7][8] Surgical resection remains the primary treatment modality for oral cavity VC, and rates of PORT range from 10% to 18%. 9,10 However, the benefit of PORT is unclear, and may actually reduce survival.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent cross-sectional population analysis of the Surveillance, Epidemiology, and End Results (SEER) database, Mohan et al reported that patients treated with PORT trended toward worse overall survival (OS) compared to those treated with surgery alone (71.4 and 117 months, respectively; P = .12). 5 There continues to be debate regarding the role of PORT in the management of oral cavity VC given its low metastatic potential, paucity of data surrounding outcomes after adjuvant treatment, and previous reports of anaplastic transformation following radiation therapy (RT). [11][12][13] Recent studies have disputed the concept of radiation-induced anaplastic transformation, and argue that such reports are reflective of tissue sampling errors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[11] The study done by Mohan et al also reports that verrucous carcinoma which is treated with adjuvant radiotherapy has a worse overall survival and disease-specific survival as compared to both verrucous carcinoma treated with surgery alone and SCC treated with surgery and adjuvant radiotherapy. [12]…”
Section: Discussionmentioning
confidence: 99%